2008
DOI: 10.1073/pnas.0804956105
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of MDA-5/RIG-I-dependent innate immunity: Independent evolution by domain grafting

Abstract: Interferons (IFNs) comprise a family of secreted proteins (cytokines) produced by cells following virus infection and create an antiviral state in neighboring cells (1-6). The relationship between IFN and viral infection is well documented and supported by studies employing neutralizing antibodies and IFN-receptor knockout mice, which document a direct role for IFN in mediating host defense against viruses (7,8). Moreover, IFNs are now recognized as multifunctional molecules that also provide defense against b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 64 publications
1
86
3
Order By: Relevance
“…The 2′-O-methylation of 5′-end nucleotide is the essential modification to avoid recognition by RIG-I and residue H830 is the sensor for this modification on Cap-1 RNAs. RIG-I is found only in higher eukaryotes like humans and other vertebrates, and this coincides with the emergence of 2′-O-methyltransferases over the course of evolution (28). All human cellular mRNAs bear either Cap-1 or Cap-2 structures, and based on our findings such RNAs cannot activate RIG-I, regardless of single-stranded or double-stranded ends.…”
Section: Rig-i Accommodates the M7g Cap Without Perturbation Of The Pppmentioning
confidence: 89%
“…The 2′-O-methylation of 5′-end nucleotide is the essential modification to avoid recognition by RIG-I and residue H830 is the sensor for this modification on Cap-1 RNAs. RIG-I is found only in higher eukaryotes like humans and other vertebrates, and this coincides with the emergence of 2′-O-methyltransferases over the course of evolution (28). All human cellular mRNAs bear either Cap-1 or Cap-2 structures, and based on our findings such RNAs cannot activate RIG-I, regardless of single-stranded or double-stranded ends.…”
Section: Rig-i Accommodates the M7g Cap Without Perturbation Of The Pppmentioning
confidence: 89%
“…In mammals, RIG-I and Mda5 are shown to preferentially sense dsRNA during RNA virus evasion, to elicit IFN antiviral response (Yoneyama and Fujita, 2009). These gene counterparts also exist in fish genome (Sarkar et al, 2008;Zhang et al, 2007;Zou et al, 2009). Actually, some important genes, including RIG-I, Mda5, MITA, TBK1, IRF3 and IRF7, which are known to play essential roles in virus-activated mammalian IFN response (Tamura et al, 2008), have been identified in crucian carp (Jiang et al, 2009;Zhang et al, 2003a;Zhang et al, 2007;Zhang et al, 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…Since fish express a typical MAVS involved in IFN production, they should also possess specific sensors of the RLR pathways that would be counterparts of mammalian RIG-I and MDA5. A recent survey of sequences sharing the MDA-5 and RIG-I domain arrangement (CARD1-CARD2-helicase-DEAD/DEAH) revealed that fish possess likely counterparts of MDA5 but not RIG-I, suggesting that the complete RLR pathway may have originated recently in the tetrapod or even the mammalian lineage (30). Combining in silico analysis and RACE, we identified a fish transcript encoding a protein most similar to RIG-I, with two CARDs and a helicase motif.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the RLRs, sequence data present in GenBank suggest that fish also possess RIG-I-like molecules and several of the downstream signaling molecules found in mammals. A recent extensive study of RLR evolution concluded that orthologs of MDA5, but not RIG-I, were found in fish, suggesting that MDA5 appeared before RIG-I in vertebrate evolution (30). In the present study, we cloned MAVS-like cDNAs from several fish species (including salmon and zebrafish) and showed that they were true orthologs of mammalian MAVS.…”
mentioning
confidence: 95%